Analysis of Character Education Values in Wewarah Osing - Ismaul Fitroh; Disman Disman; Kokom Komalasari; Mamat Ruhimat (STAI Hubbulwathan Duri, 2023)
Osing is a native tribe of Banyuwangi located in East Java Province. The Osing tribe owns a variety of unique and interesting cultures to learn about. One of the cultures from the Osing tribe is wewarah Osing. In wewarah Osing, there are many wise words with good character values which are able to strengthen the nation’s character. Therefore, this study aimed to analyze the character values contained in wewarah Osing. The study method applied in this research is a qualitative method through a literature study as the data collection technique. Whereas the research data are obtained through creating a topic mapping in relation to character education and Osing culture found from Google Scholars, Crossref, ResearchGate, related books and journals, accessed from 10 March 2023 to 26 June 2023. The result of the study showed in wewarah Osing, traditional proverbs to support or used to strengthen the national character. These good characters namely discipline, social care, hard work, responsible, and religious.